Social Harmony through Local Wisdom: Da'wah in the Kalang Obong Tradition - Riyadi, Agus; Sulistio, Sulistio; Karim, Abdul (Jurnal Dakwah Risalah, 2024)
This study aims to determine the value of local wisdom and how da'wah through local wisdom affects social harmony in the Kalang Obong ceremony. This research is qualitative. Data collection techniques used in-depth interviews, participant observation, and documentation. The results showed that: First, the description of the reality of the Kalang community, which is a Javanese sub-ethnicity that has the same life as the Javanese community; the difference is related to identity so that it gives rise to the lonjong tradition as part of local wisdom. Second, the local wisdom values in this ceremony include religious values, Birul Walidain values (respect and obedience towards parents), tolerance, social, discipline, economic, and moral values. Third, the form of da'wah through local wisdom values in realizing community harmony includes da'wah bi al-Hikmah (da'wah carried out with wisdom), where da'wah al-hikmah in this ceremony contains the form of da'wah bil hal (da'wah through concrete actions and daily behavior), amar ma'ruf nahi munkar (commanding goodness and preventing evil), da'wah theology (da'wah that focuses on theological aspects), tazkiyah (self-purification), and tausiyah (advice).